Analisis dan Perancangan Jaringan Saraf Tiruan untuk Mengidentifikasi Tingkat Kematangan Buah Belimbing Manis (Averrhoa carambola L.) - Dahwanu, Oki; Sarjono, Sarjono (Jurnal Manajemen Sistem Informasi, 2019)
Starfruit is one of the fruits that are widely cultivated in Indonesia. But at this time sorting of starfruit is stilldone manually by humans, consequently resulting in a uniform level of maturity that is not good. For thisreason, a system is needed that can identify the level of maturity of starfruit with artificial neural networks.The main problem of designing artificial neural networks is how to analyze and design an artificial neuralnetwork architecture in order to determine the maturity level of sweet starfruit properly. This study aims todesign artificial neural networks with backpropagation method to identify the maturity level of starfruit.From the results of the study, the best configuring of backpropagation artificial neural network model is amodel of artificial neural networks with 3 inputs, 11 hidden layer neurons and 3 outputs (3-11-3). With thisconfiguration, artificial neural networks are able to identify the level of maturity with a success rate of 95.8%of 48 starfruit test data.